An updated checklist to the biodiversity data of ladybeetles (Coleoptera: Coccinellidae) of the Azores Archipelago (Portugal) - Soares, António O. (2022)
BACKGROUND: A recently-published review from 2021 presents a comprehensive checklist of ladybeetles of Portugal, including the Azores and Madeira Archipelagos. Until then, the available information was very scattered and based on a single revision dating back to 1986, a few international catalogues and databases, individual records and studies on communities of agroecosystems. However, no information was available on faunal composition across the Azorean islands and their habitats, using standardised inventories. Here, we present data about the biodiversity of ladybeetles and their distribution and abundance in five Islands of the Azores (Faial, Graciosa, Pico, São Jorge and São Miguel). Surveys included herbaceous and arboreal habitats from native to anthropogenic-managed habitats: ruderal road vegetation, vegetable garden, mixed forest of endemic and non-native host plants, coastal prairies, coastal mixed vegetation, cornfields and urban areas. We aimed to contribute to the ongoing effort to document the terrestrial biodiversity of Portugal, including the Archipelago of the Azores, within the research project AZORESBIOPORTAL–PORBIOTA (ACORES-01-0145-FEDER-000072). NEW INFORMATION: In this study, a total of 1,487 specimens of Coccinellidae belonging to 19 species are reported for several habitats. The listed species are from one single sub-familiy (Coccinellinae) and six tribes; Chilocorini (one species), Coccidulini (three species), Coccinellini (six species), Noviini (one species), Scymnini (seven species), Stethorini (one species). The number of species collected per island differed; Faial (10 species), Graciosa (four species), Pico (seven species), São Jorge (seven species) and São Miguel (12 species). For six species, new island records are given. Currently, the number of species known to occur in the Azores are 32, including two doubtful records. The majority of species are Scymnini, being Scymnus (Scymnus) interruptus (Goeze, 1777) and Scymnus (Scymnus) nubilus Mulsant, 1850, the most abundant species (relative abundance 71.1%). This database will be the baseline of a long-term monitoring project allowing assessment of the impact of ongoing global changes in the distribution and abundance of ladybeetles.